In vitro anticancer properties and biological evaluation of novel natural alkaloid jerantinine B - Qazzaz, Mohannad E.; Raja, Vijay J.; Lim, Kuan-Hon; Kam, Toh-Seok; Lee, Jong Bong; Gershkovich, Pavel; Bradshaw, Tracey D. (Elsevier, 2016)
Natural products play a pivotal role in medicine especially in the cancer arena. Many drugs that are currently used in cancer chemotherapy originated from or were inspired by nature. Jerantinine B (JB) is one of seven novel Aspidosperma indole alkaloids isolated from the leaf extract of Tabernaemontana corymbosa. Preliminary antiproliferative assays revealed that JB and JB acetate significantly inhibited growth and colony formation, accompanied by time- and dose-dependent apoptosis induction in human cancer cell lines. JB significantly arrested cells at the G2/M cell cycle phase, potently inhibiting tubulin polymerisation. Polo-like kinase 1 (PLK1; an early trigger for the G2/M transition) was also dose-dependently inhibited by JB (IC50 1.5 µM). Furthermore, JB provoked significant increases in reactive oxygen species (ROS). Annexin V+ cell populations, dose-dependent accumulation of cleaved-PARP and caspase 3/7 activation, and reduced Bcl-2 and Mcl-1 expression confirm apoptosis induction. Preclinical in silico biopharmaceutical assessment of JB calculated rapid absorption and bioavailability >70%. Doses of 8–16 mg/kg JB were predicted to maintain unbound plasma concentrations >GI50 values in mice during efficacy studies. These findings advocate continued development of JB as a potential chemotherapeutic agent.